Characterization and typology of goat production systems in the Southern Highlands of Peru - Emmanuel Alexander Sessarego; Fritz Carlos Trillo; David José Godoy; Walter Palomino-Guerrera; Juancarlos Alejandro Cruz (Veterinary World)
Background and Aim: Characterizing local animal production systems is crucial for sustainable livestock development. This study aimed to characterize the diversity of goat production systems in the Highlands of Chincha province, Ica, Peru.